RELASI PERSEPSIONAL KODRAT TERHADAP GENDER PERSPEKTIF AL-QURAN - Achmad, Danial (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2025)
Gender, which is understood as a status formed by social and cultural, is different from nature that is perceived as innate in creation. Thus, gender equality can be built as the truth of total cooperation between men and women in social and domestic roles. In fact, the perception that tries to build the totality of equality between men and women, has a gap. If the total integration of the two is still carried out, it is tantamount to imposing an idea on reality. Women have different physical biology than men, so there are certain parts of the role that are not possible for her to do so, such as the heavy and high-risk work that men do. Efforts to unravel and research these problems use a type of library research. The step is to examine the verses of the Qur'an and relevant literature on the relationship between nature and gender with an analytical-thematic approach through a psychoanalytic-biological approach. As a result, the totality of gender equality integration between men and women is impossible, because nature binds and limits gender. The equality that can be obtained is the equality of obtaining rewards, becoming a caliph on earth and both as slaves. Other equality is certain areas that can be borne by nature so as not to harm and damage women, such as writing, services, secretarial work, parenting and care or in executive and professional circles